Melville and the Vortex Theory of Matter - Paweł Stachura (European Journal of American Studies)
The brief reference to the Cartesian vortex in Moby-Dick has already been discussed in numerous specialized articles, usually in terms of the history of ideas, e.g. in two articles by D. C. Leonard (1979; 1980). By itself, a vortex is an appropriate image for being immersed, obsessed, absorbed, and blended into objectivity, but the paper will focus on another, non-Cartesian vortex, which was emerging in the 1850s as the so-called vortex theory of matter. The point of this “hydrokinetic theory of matter” was that it was a “unitary continuum theory” of a “Universal Plenum,” conceived initially on the basis of Herman von Helmholtz’s work on hydrodynamics. In 1859, the German physicist demonstrated mathematically that stable vortex rings could exist indefinitely in a (theoretical) continuous elastic fluid, rather like the remarkably stable smoke rings blown by guns or as a smoking trick. For a time, the vortex atom was recognized as a very promising idea on the cutting edge of science. In literary fiction, the vortex atom translated into curious imagery of a claustrophobic universal plenum, matter and soul combined, organized by intermeshing vortices, and leaving no possible room for a hovering freedom in empty space. In a universe based on the vortex theory of matter, a subject is not in a vortex, but is itself a vortex, continuously meshing with other vortices, in a basket-like, tightly knit lattice that comprises everything. Melville’s imagery related to matter and vortices seems to be one of the early instances of the simultaneous fascination and dismay provoked by the vortex theory of matter in the second half of the nineteenth century, not among scientists, but among the non-scientific general audience. The article focuses on Clarel, comparing three different images of the vortex with imagery from contemporary popular scientific articles. Additional examples from Moby-Dick, Pierre, and Billy Budd are discussed as contexts illustrating the variety of meaning attached by Melville to the vortex.